2000
DOI: 10.1097/00003246-200009000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic study of the distribution of microcirculatory blood flow in multiple splanchnic organs in septic shock

Abstract: Changes in microcirculatory blood flow in the splanchnic organs are heterogeneous, both in early hypodynamic and in hyperdynamic septic shock, and cannot be predicted from changes in systemic or regional flows. Microcirculatory blood flow in the jejunal mucosa remains constant during early septic shock, whereas pancreatic blood flow decreases significantly more than regional flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 37 publications
5
84
0
2
Order By: Relevance
“…Animal studies also showed changes of microcirculatory blood flow in organs were heterogeneous, and pancreatic blood flow decreased more significantly than regional flow during early septic shock. Hiltebrand et al [12] used severe septic shock models of pigs to study dynamic distribution of microcirculatory blood flow in multiple splanchnic organs during septic shock, and they found that systemic and regional flows decreased by 50% during the first 240 minutes, while microcirculatory fl ow signifi cantly decreased in the pancreas, liver, colon, kidney and stomach by 56%, 49%, 47%, 44%, and 41%, respectively. Endotoxin was found to play an important role in septic shock patients with pancreatic damage, activating complements and coagulation systems, generating bradykinins and cytokines, and causing shock and damage to various organs including the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies also showed changes of microcirculatory blood flow in organs were heterogeneous, and pancreatic blood flow decreased more significantly than regional flow during early septic shock. Hiltebrand et al [12] used severe septic shock models of pigs to study dynamic distribution of microcirculatory blood flow in multiple splanchnic organs during septic shock, and they found that systemic and regional flows decreased by 50% during the first 240 minutes, while microcirculatory fl ow signifi cantly decreased in the pancreas, liver, colon, kidney and stomach by 56%, 49%, 47%, 44%, and 41%, respectively. Endotoxin was found to play an important role in septic shock patients with pancreatic damage, activating complements and coagulation systems, generating bradykinins and cytokines, and causing shock and damage to various organs including the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, despite the hyperdynamic circulatory state, micro vascular flow appears to be unchanged or even decreased [42,43] . Intrahepatic blood flow is redistributed, blood is channeled away from contracted to dilated vessels reducing the perfused sinusoidal area.…”
Section: Liver Circulation In Sepsismentioning
confidence: 97%
“…Moreover, despite presenting a hyperdynamic systemic circulation, the mucosa hypoperfusion in gastric, small intestine and colonic tissue commonly develops into sepsis (68). Gastrointestinal mucosa has been described as one of the highest metabolically active tissues under conditions of sepsis (69,70) and although no clear association has been found, gut flow and metabolic changes appear to be heterogeneous (71)(72)(73)(74). During compromised mucosal tissue, the reaction mechanism has been proposed as an increase of oxygen extraction (75).…”
Section: Gastrointestinal Perfusion Monitoringmentioning
confidence: 99%